Disain Wisata Desa Triwidadi, Kapanewon Pajangan, Kabupaten Bantul - Zona A - Setiadi, Amos; Binarti, Floriberta; Tesalonika, Clara (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
“Pengabdian pada Masyarakat” was done to assist partners by designing tourism-supporting facilities. The intended outcomes of this Pengabdian kepada Masyarakat are the increase in tourist visits and its effect on the welfare of the surrounding local communities. The Pengabdian kepada Masyarakat was conducted in three steps, i.e., Preparation and Data Collection, Location Survey and Interviewing Partners, and Drafting Concepts and Designs. This tourist destination has a potential artificial lake, but no tourism support facilities exist, so it can not be developed. Tourism support facilities are essential because they serve as tourist attractions when in a tourist destination. The problem in this design is how the creation of this attraction is aligned with the local natural conditions. The program’s conclusion is a design of tourism-supporting facilities in Triwidadi village such as Resto, Gazebo, Viewing Post, Toilet, and Playground.